Climate counts: a multilevel validation of the EssenCES in Romanian correctional settings - Toma, Roxana Andreea; Răducan, Raluca Maria; Matichescu, Marius Lupsa; Andelin, Emanuel Ionuț; Banse, Rainer (Frontiers in Psychology, 2025)
IntroductionThe social climate in prisons is associated with better mental health and increased participation in activities.MethodIn a validation study, we examined the predictive validity of the EssenCES for the Romanian prison system. The sample included 566 inmates and patients as well as 175 staff members, 741 in total.ResultsThe Romanian version of EssenCES with the three scales Patients’/Inmates’ Cohesion and Mutual Support, Experienced Safety and Therapeutic Hold showed good psychometric properties for prisons and forensic hospitals. Inmates and staff rated the prison climate slightly differently, with staff having a more positive view of therapeutic support than inmates, and inmates having a more positive view of the security on the ward. Staff in semi-open and maximum security regimes reported higher Patient Cohesion scores than inmates in regular prisons, while staff in forensic hospitals reported lower Patient Cohesion scores than inmates in the same settings.DiscussionTaken together, the findings demonstrate the utility of multilevel and multivariate approaches in clarifying how regime and role shape prison climate, informing practice across forensic and correctional settings.